Efficacy of Cognitive Training on Executive Functions in Healthy Older Adults : a Systematic Review with Meta-Analysis of Randomized Controlled Trials - Olegário, Raphael Lopes (2023)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Psicologia, Departamento de Processos Psicológicos Básicos, Programa de Pós-Graduação em Ciências do Comportamento, 2023.